HUMAN RIGHTS PROTECTION TO WOMEN IN TIMES OF NATURAL DISASTERS IN THE FRAME OF ASEAN REGULATIONS - Puspita, Natalia Yeti (UI Scholars Hub, 2012)
In the last decade, the occurrences of natural disasters in ASEAN (Association South East Nations) regions have intensified. ASEAN was prone natural disasters such as earthquakes and tsunamis which frequently hit the region and as we know natural disasters can happen anytime. In a disaster management process, an understanding of law especially in the context of human rights protection is crucially needed, including in the prior disaster phases, in the emergency-disaster phase, and in the after-disaster phase. If such elements are excluded, it may postpone the implementation of humanitarian aid program and may even be a threat to the victims’ rights. This situation is more concretely illustrated in the after disaster phase, where law is needed to protect the vulnerable societies, namely in handling the problem of illegal adoption of an orphan child, child and women trafficking, and violation to marginal groups and discrimination in humanitarian aid distribution. The understanding human rights law in disaster situation will be tested in the field, as it often occurs that the law is not compatible with the situation, or that it is not complete or contrary to the system of law, or the lack of understanding regarding the law. Human rights are the basic rights which must be conferred to everyone. The international law and human rights posted the obligation to the state to protect, respect, and fulfill those rights without discrimination. ASEAN as a Regional International Organization has had the ASEAN Agreement on Disaster Management and Emergency Response and also The ASEAN Coordination Center for Humanitarian in related with disaster management.